Infective Complications of Endobronchial Ultrasound-Transbronchial Needle Aspiration (EBUS-TBNA) and Clinical Biomarkers: A Concise Review - Pinelopi Bosgana; Dimitrios Ampazis; Vasileios Vlachakos; Argyrios Tzouvelekis; Fotios Sampsonas (Diagnostics)
EBUS-TBNA is the most common interventional pulmonology procedure performed globally and remains the cornerstone of the diagnosis and staging not only of lung cancer but also for other neoplastic, inflammatory, and infective pathologies of the mediastinum. Infective complications of EBUS-TBNA are underreported in the literature, but the constantly rising incidence of lung cancer is leading to an increasing number of EBUS-TBNA procedures and, therefore, to a significant number of infective complications, even 4 weeks following the procedure. In this review we attempt to summarize the risk factors related to these infective complications, along with useful biomarkers that can be used to identify patients that might develop infective complications, to facilitate the prediction or even prompt treatment of these.